2021
DOI: 10.1111/jcmm.16988
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‐34b/c regulates mucus secretion in RSV‐infected airway epithelial cells by targeting FGFR1

Abstract: Respiratory syncytial virus (RSV) infection in airway epithelial cells is the main cause of bronchiolitis in children. Excessive mucus secretion is one of the primary symbols in RSV related lower respiratory tract infections (RSV‐related LRTI). However, the pathological processes of mucus hypersecretion in RSV‐infected airway epithelial cells remains unclear. The current study explores the involvement of miR‐34b/miR‐34c in mucus hypersecretion in RSV‐infected airway epithelial cells by targeting FGFR1. First, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In humans, mucin expression during infection is regulated by a panoply of miRNAs, namely miR-34b/c (Li et al. 2021 ), miR-146a (Zhong et al. 2011 ), miR-378 (Skrzypek et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, mucin expression during infection is regulated by a panoply of miRNAs, namely miR-34b/c (Li et al. 2021 ), miR-146a (Zhong et al. 2011 ), miR-378 (Skrzypek et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs have been shown to regulate the glycan biosynthetic enzymes and regulate the expression of mucin genes in the respiratory tract of humans, including miR-34b/c (Li et al. 2021 ), miR-146a (Zhong et al. 2011 ), miR-378 (Skrzypek et al.…”
Section: Introductionmentioning
confidence: 99%
“…NAC was previously found to restore the sensitivity of gefitinib-resistant lung cancer cells to gefitinib that is a major epithelial growth factor receptor tyrosine kinase inhibitor, suggesting the inhibitory effects of NAC on EGFR activation in epithelial cells [24]. With regard to NAC inhibition on mucin hypersecretion caused by RSV infection [25], a previous study, similar as our study, reported that NAC reduce airway inflammation and responsiveness, goblet cell hyperplasia, and lung fibrosis by increasing levels of ROS, nuclear factor erythroid 2-related factor 2, and MUC5AC protein [26]. The present study analyzed the HSPA6 expression in RSV-infected BEAS-2B cells treated with and without NAC.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, some miRNAs show prominent roles in regulating airway mucus homeostasis. For example, it was found that miRNA-34b/c regulated mucus secretion in RSV-infected airway epithelial cells and that miRNA-330 regulated IL-13-induced MUC5AC secretion in human bronchial epithelial cells [ 14 , 53 ]. In addition, tumour necrosis factor- α promoted airway mucus hypersecretion by inhibiting miR-146a-5p and miR-134-5p levels [ 54 ].…”
Section: Discussionmentioning
confidence: 99%